IMPLEMENTASI KONSEP ILMU TAUHID DALAM KITAB AQIDATUL AWAM DAN RELEVANSINYA TERHADAP PEMBENTUKAN AKHLAK SANTRI DI PONDOK PESANTREN AL-HUDA BOGEM DIWEK JOMBANG - Arsyadani, Fahry; Inayatul Ilahiyah, Iva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to explain how the concept of monotheism contained in the Book of Aqidatul Awam is applied and its relationship with the formation of morals for students at the Al-Huda Islamic Boarding School Bogem Diwek Jombang. The method used in this research is a qualitative approach with a case study type. The research subjects included Islamic boarding school caregivers, ustadz, and Islamic boarding school students who were involved in studying the Book of Aqidatul Layman. Data was collected using observation, interviews and documentation techniques. For data analysis, the data reduction, data presentation and conclusion drawing stages were used. Data validity was tested through triangulation of sources and techniques. The findings of this research indicate that the application of the concept of monotheism in the Aqidatul Layman Book is carried out through the activities of memorizing, understanding and realizing the values of monotheism in everyday life. The learning material includes the characteristics of Allah and the Messenger, as well as the pillars of faith which are the foundation for the formation of students' religious awareness. The formation of morals is carried out through habits of worship, example, discipline, a sense of responsibility, as well as developing good relationships with God, fellow humans, oneself and the surrounding environment. This study found that understanding monotheism (tauhid) is closely related to the moral development of students. Internalized monotheism values in students can facilitate the development of sincerity, honesty, discipline, responsibility, humility, and concern for society. Therefore, the Aqidatul Awam book serves not only as a tool for learning the faith but also as an effective medium for developing religious character and good morals in students.